2021
DOI: 10.6000/1929-6029.2021.10.18
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive Training to Improve Static and Dynamic Balance in Elderly

Abstract: Background: The risk of falls is a major cause of disability in older adults. A single fall, for the elderly, increases the risk of frequent falls and often causes an increased fear of falling again, which can become debilitating. Objectives: The purpose of the present study was to test the effects of 12 weeks of proprioceptive training on the static and dynamic balance of older adults who have experienced at least one fall without compromising consequences. Method: The sample consisted of older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“… 33 , 40 , 41 In two studies focused on proprioceptive training, exercises were performed exclusively with eyes open. 33 , 42 Additional studies, 35 , 43 incorporated exercises like rolling a ball with one foot while standing and standing on a foam cushion with the alternate foot. The variations in methodologies and exercises across these studies underscore the ambiguity surrounding the definition of proprioceptive training.…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 40 , 41 In two studies focused on proprioceptive training, exercises were performed exclusively with eyes open. 33 , 42 Additional studies, 35 , 43 incorporated exercises like rolling a ball with one foot while standing and standing on a foam cushion with the alternate foot. The variations in methodologies and exercises across these studies underscore the ambiguity surrounding the definition of proprioceptive training.…”
Section: Discussionmentioning
confidence: 99%
“…It is also defined as the ability to maintain an upright posture and to keep the centre of gravity (COG) within the limits of the base of support (Jonsson et al, 2004) (Mochizuki et al, 2006). McGuine et al (2000) have reported higher injury incidence in athletes with poor postural control and it was suggested that balance postural control may be influenced by several aspects such as muscles and proprioception (Raiola et al, 2020) (Esposito et al, 2021), relative position of body segments (Giustino et al, 2021) and even anthropometric parameters and somatotypes (Allard et al, 2001) (Farenc et al, 2003). In fact, somatotypes can be considered an overview of the physical characteristics of the human body (Carter & Heath, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits that regular physical activity can bring to individuals of all ages and genders are well known [1,2], such as reducing the risk of morbidity and mortality and the risk of contracting many chronic diseases, such as coronary artery disease, diabetes mellitus and cancer [3], also reducing the risk of falls in the elderly [4] and improving the level of independence of people with disabilities. The practice of sport makes it possible to productively satisfy human needs linked to the experience of play, movement, competitiveness, and group life.…”
Section: Introductionmentioning
confidence: 99%